THE INCIDENCE OF FALLS AND RELATED FACTORS IN THE ELDERLY LIVING IN RESIDENTIAL HOMES - (:unkn) unknown (GUNES KITABEVI LTD STI, 2012)
Introduction: The aim of this study is to explore the incidence of falls and related factors in the elderly living in residential homes (RHs). Materials and Method: This prospective study represents 1288 individuals living in 25 RHs in the Anatolian region of Istanbul. We included 183 volunteers aged >= 65 years, without any speech, understanding, expression disordersor any serious diseases who scored >= 24 in Mini Mental Status Examination and who were still living in the RH after one year. In the first visit we inquired socio-demographic features, health problems, assistive devices, falling history in the past 6 months and medication use and we evaluated daily living activities and blood pressure. The following year we inquired changes in health status, medication use and new falls and we evaluated vision, balance and gait problems. Results: The mean age was 77.1 +/- 7.2. The fall incidence was 33.9%. Falling history in the past 6 months and systolic hypertension were identified as risk factors related with new falls (OR 3.772, 95% CI 1.852-7.682, p < 0.001; OR 2.184, 95% CI 1.052-4.534, p=0.036). Conclusion: In our study, falling history and systolic hypertension are identified as risk factors for new falls. Identifying these risk factors may help preventing falls and planning individual preventive procedures.
Keywords: Risk factors; Nursing homes; Activities of Daily Living; Prospective Study; Prevention & control; Hypertension; NURSING-HOME; RISK-FACTORS; ASSOCIATION; POPULATION; PREVENTION; FRAIL